2011
DOI: 10.1136/gut.2009.204453
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for advanced neuroendocrine carcinomas of jejunum/ileum and pancreatic origin

Abstract: Multimodal treatment options for advanced gastroenteropancreatic neuroendocrine tumours (NET) of jejunum/ileum and of pancreatic origin are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 243 publications
0
61
0
1
Order By: Relevance
“…Kweekeboom reported the occurrence of carcinoid crisis was about 1% after peptide receptor radionuclide therapy in 510 patients. (Auernhammer and Goke, 2011) Carcinoid crisis can be engendered by anesthesia, medication (chemotherapy, or radiopharmaceuticals) and various invasive procedures. (Tomassetti et al, 2001) It is worth noting that the event can even occur in apparently symptomatic-stable patients and be provocated by a simple biopsy from the tumor body.…”
Section: Introductionmentioning
confidence: 99%
“…Kweekeboom reported the occurrence of carcinoid crisis was about 1% after peptide receptor radionuclide therapy in 510 patients. (Auernhammer and Goke, 2011) Carcinoid crisis can be engendered by anesthesia, medication (chemotherapy, or radiopharmaceuticals) and various invasive procedures. (Tomassetti et al, 2001) It is worth noting that the event can even occur in apparently symptomatic-stable patients and be provocated by a simple biopsy from the tumor body.…”
Section: Introductionmentioning
confidence: 99%
“…A large multicentre case series has reported a 5 and 10 year survival rate of 74% and 51% respectively following surgery for LM, however this does not correlate with disease free survival, as 5 year tumour recurrence has been quoted to be as high as 94-97% of patients [15]. Sarmiento et al [19] reported a case series of 170 patients of which 44% had a curative resection and 56% had a debulking of >90% of tumour load whose average 5 year survival rate was 61%, yet with a tumour recurrence rate of 84%.…”
Section: Surgical Management Of Hepatic Metastases In Neuro-endocrinementioning
confidence: 99%
“…An alternative strategy to ensure the future liver remnant is (FLR) >30% is to perform a 2 staged resection [15].…”
Section: Surgical Management Of Hepatic Metastases In Neuro-endocrinementioning
confidence: 99%
“…However, a large number of patients suffer unresectable tumor. In these cases the main objective of therapy is to control the progression [11].…”
Section: Analysis Of Costs Of Medicinal Product Lanreotide (Somatulinmentioning
confidence: 99%